Analysis and Research on Current-carrying Friction and Wear of High-speed Train Pantograph Slide and Contact Wire Based on Computer Simulation Analysis. Issue 3 (October 2020) - Wang, Ruyu; Zhang, Zhiguo; Zhong, Jialong
Abstract: High speed train has many advantages, such as large capacity, fast speed, low cost, small energy consumption, economic and environmental protection, safety and comfort, which has become an important part of high-speed railway in China. Therefore, pantograph catenary system will become an important part of high-speed train. However, due to the vibration of the high-speed train or the irregularity of the contact wire, the pantograph slide plate and the contact wire will produce an arc, which will lead to friction and wear. Therefore, under the complex environment, the pantograph slide plate and contact wire will form a mechanical and electrical wear coupling, which will make the current carrying friction and wear between the pantograph slide plate and contact wire more complex. Therefore, high-speed trains will suffer more problems, which will further restrict the speed-up of locomotives. Therefore, this paper first uses computer simulation technology to analyze the working relationship between pantograph slide plate and catenary of electric locomotive. Then, the friction and wear characteristics of pantograph slide plate and contact wire are studied by experiment.